Design and Implementation of Carrier Detection System Based on FPGA. Issue 4 (October 2020) - Zhang, Xian; Qu, Taiguo; Liu, Yiwen; Yin, Dong; Deng, Shaowei
Abstract: In order to better monitor and manage the signal transmission in the communication system and base station, and carrier detection is more effective. This paper designs a carrier(Carrier frequency) detection system based on FPGA, including system design requirements, FPGA selection, system framework design, carrier detection method design and so on. The performance indexes of the system are tested, such as carrier frequency range, carrier search time, carrier detection number and CPU consumption rate. The system has the advantages of high flexibility and good portability, and has a good application prospect in communication system, base station and other equipment.